2021
DOI: 10.3390/su13041672
|View full text |Cite
|
Sign up to set email alerts
|

Have Sustainable Development Goal Depictions Functioned as a Nudge for the Younger Generation before and during the COVID-19 Outbreak?

Abstract: Sustainable Development Goals (SDGs) and their corresponding logos have become ubiquitous in Japan. While not legally binding, they allow us to choose how to contribute or not to the SDGs. Considering that SDGs share characteristics with nudges, we investigated whether SDGs, with their term and logos, have functioned as a nudge before and during the COVID-19 outbreak. Using Japan as a case study, we analyzed newspaper articles to explore how the term SDGs has spread before and during the outbreak. We also cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Recent media analysis has revealed that the number of newspaper articles explaining and promoting the SDGs has rapidly increased over the years, and more sustainability-related information in these media has the potential to significantly enhance citizens’ (and students’) environmental awareness and behaviors (Sakurai et al 2021 ). A survey conducted among Japanese university students in 2019 revealed how the idea of SDGs has taken root; many students realized the importance of sustainability awareness and engaged in pro-environmental behaviors (Uehara and Sakurai 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent media analysis has revealed that the number of newspaper articles explaining and promoting the SDGs has rapidly increased over the years, and more sustainability-related information in these media has the potential to significantly enhance citizens’ (and students’) environmental awareness and behaviors (Sakurai et al 2021 ). A survey conducted among Japanese university students in 2019 revealed how the idea of SDGs has taken root; many students realized the importance of sustainability awareness and engaged in pro-environmental behaviors (Uehara and Sakurai 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the COVID-19 pandemic could have strengthened students’ perceived importance of environmental conservation. For example, previous studies have shown that students’ environmental awareness toward sustainability and willingness to protect the environment was enhanced after watching news about COVID-19 (Uehara and Sakurai 2021 ). A previous study that analyzed international survey datasets including the World Values Survey revealed how generalized trust (e.g., how much people trust others) could narrow the gap between environmental concern and pro-environmental behavior (Tam and Chan 2018 ), and various factors including trust level should be explored and analyzed in the future study to identify why students’ environmental concern changed over four years.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been an increase in awareness. In particular, the pandemic period has resulted not only in a staggering number of deaths globally, but it has also increased awareness of sustainable issues [3]. Sustainability covers multiple aspects of resource use and society [4].…”
Section: Sustainability: An Overviewmentioning
confidence: 99%
“…To avoid the negative effects of climate change, sustainable goals have been adopted in recent decades [9]. These are guided by the concept of sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%